The Perception of Learners on the Role of Facebook Messenger as a Tool for Academic Communication - Manriquez, Lavyrl; Roque, Ruffy Mae; Serat, Michelle; Siat, Gregg (Technium Social Sciences Journal, 2025)
This study explored how learners perceive Facebook Messenger as an academic communication tool and how it relates to demographic profiles in terms of age, gender, family income, and occupations concerning both parents. Using frequency analysis, descriptive statistics, and correlation tests, this study surveyed 39 respondents aged 9–13, where the largest number fell within the ages of 10 and 11. Results indicated that students find Messenger easy to use and accessible, helpful in academic engagement, and rated as "Very Good" to "Excellent" in most aspects. However, among the limitations of this app, its message handling and distractions were claimed. Most of the demographic variables were not significantly associated with their views except by mother’s occupation and gender influencing specific categories. All these findings emphasize Messenger as a prospective reliable academic tool, emphasizing areas of improvement to exploit its potential in educational communication. Keywords: Messenger, Academic Communication, Learner’s Perception, Educational Technology, Communication Platforms.